Impact of the COVID-19 Pandemic on the Incidence and Characteristics of Culture-Positive Microbial Keratitis at a Tertiary Eye Hospital in the UK - Michaels L; Richardson J; Walkden A; Carley F (Clinical Ophthalmology, 2022)
Luke Michaels,1 Jay Richardson,1 Andrew Walkden,1,2 Fiona Carley1,2 1Manchester Royal Eye Hospital, Manchester, UK; 2Centre for Ophthalmology and Vision Sciences, Faculty of Medical and Human Sciences, University of Manchester, Manchester, UKCorrespondence: Andrew Walkden, Manchester Royal Eye Hospital, Oxford Road, Manchester, Greater Manchester, M13 9WL, UK, Tel +44 161-276-1234, Email walkdenandrew@gmail.comPurpose: The COVID-19 pandemic has led to drastic changes to the daily lives of those living in the United Kingdom. We hypothesized that the effect of the imposed lockdown on both behaviour and social interaction has the potential to influence the characteristics of microbial keratitis presenting locally to Manchester Royal Eye Hospital — a major tertiary eye centre in the UK.Methods: We conducted a retrospective case-note review of all positive corneal scrape cultures identified by our local microbiology laboratory during the year since the announcement of lockdown measures in the UK (23 March 2020 to 23 March 2021). Culture results were compared with previously collated, published “baseline” data from prior to the onset of the COVID-19 pandemic (2004– 2019). Statistical analysis was undertaken, predominantly looking at the incidence of microbial keratitis and the variety of cultured pathogens.Results: A total of 6243 corneal scrape results were reviewed. Comparison of data between the COVID-19 pandemic and subsequent lockdown did not show a significant change in the incidence of culture-positive microbial keratitis: mean annual positive samples during 2004– 2019 were 128 (35%) vs 91 (29%) during lockdown (P=0.096). No statistically significant shifts in the incidence of organism subtypes — fungi, acanthamoeba, Gram-positive bacteria, or Gram negative bacteria — were identified (P=0.196, 1, 0.366, and 0.087, respectively).Conclusion: Contrary to our hypothesis, our results suggest that the COVID-19 pandemic did not alter the incidence or characteristics of microbial keratitis presenting to Manchester Royal Eye Hospital in the year following the implementation of lockdown measures in the UK.Keywords: COVID-19, keratitis, microbiology, microbial keratitis